Sosialisasi Pembuatan dan Pemasaran Bucket Melalui Media Sosial Instagram Bagi Masyarakat Kota Palopo - Lestari, Ayu; Aini, Nurfauziah; Barim, Nuranisah; Tahier, Ilham; Ratnawati (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
The bouquet business is an independent small business where the capital for the business comes from personal funds. Which is engaged in the arts because the bouquet is one of the business objects favored by the public because of its aesthetics. The purpose of this research is to find out and analyze the use of social media as a promotion and marketing strategy for Bouquet to many people. The methods used in this activity are: input, process, output (product) and evaluation methods. Our input method first determines students' interests, and looks at some of the products that have been marketed so that they can help us determine prices that are adjusted to the location and economy of students. After that we conduct a feasibility study on the business that we will run, namely by knowing whether this business has long-term business prospects. Process (production), the process of making a bouquet of flowers starting from the preparation of tools and materials until the bouquet is ready to be promoted. Then the output is handicrafts that are ready to be used and marketed via Instagram social media. The last is evaluation, which is the stage where the flower bouquet product has been completed. The conclusion of this journal is that the PKM-K Program provides opportunities for students to practice entrepreneurship and understand very comprehensive entrepreneurial concepts. The PKM-K program builds student enthusiasm to continue doing business with their craft skills. The PKM-K program utilizes social media Instagram as a market palace.